An Analyzing the Enforcement of Fines on Foreign Offenders of Fisheries Crimes in the Indonesian Exclusive Economic Zone (IEEZ) - Tatik Sunatri; Suud, Aghia Khumaesi; Penny Naluria Utami (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Indonesia has vast and diverse fisheries potential, as the sea accounts for approximately 70 percent of the territory. Consequently, numerous foreign nationals sail in the Indonesian Exclusive Economic Zone (IEEZ) for fishing and many of them violate the regulations concerning resource utilization, conservation, and management within the IEEZ. However, based on the current legal provisions, foreign offenders are only subject to monetary fines or, in some cases, imprisonment. Regrettably, in practice, many foreign suspects fail to pay the imposed fines or opt for imprisonment as a substitute, burdening the Attorney General's Office and even the state itself. This analysis uses normative juridical methods and qualitative data to evaluate the enforcement of criminal fines on foreign perpetrators of fisheries crimes within the Indonesian Exclusive Economic Zone (IEEZ). This research examined the effectiveness of enforcing criminal fines on foreign perpetrators, highlighting issues such as the inadequate enforcement of legal regulations, the ineffectiveness of the existing legal structure in imposing criminal fines on all individuals convicted of fisheries crimes in the IEEZ, and the prevailing shortcomings in the legal culture.